Riset Pasar Produk Kecap Coconut Aminos : (Studi Kasus Coconut Aminos “Gulapa” PT. Berkat Petani Indonesia ) - Dharmawan, Budi; Widyarini, Indah; Satriani, Ratna; Sudarmadji, Arief; Novia, Rifki Andi; Sakhidin; Karseno; Sunendar (JURNAL AGRICA, 2025)
Consumer awareness of a healthy lifestyle is driving an increase on demand for food products that are low in sodium, gluten-free, and made from natural ingredients. Coconut aminos with the brand "Gulapa" is one of the new products to meet the demand made by PT. Berkat Petani Indonesia. For this reason, market research is needed regarding the position of the product from the consumer's perspective. This study was aimed to analyze the market potential of coconut aminos "Gulapa", evaluate consumer preferences, and identify effective marketing strategies. The research period was 5 (five) months in 2024 in Banyumas, Purbalingga, Purwokerto, and Cilacap Regencies, Central Java Province. The descriptive analysis method was used with data collection using qualitative approach through observation and interviews, as well as secondary data analysis. Data was analyzed using worksheet as a tool to represent what was to be known and researched. The results of the worksheet analysis can be concluded that most consumers were not familiar with coconut aminos products, but have high interest in trying them. Consumer preferences for choosing healthy coconut aminos include a priority order in the form of brand reputation, taste, price, and ease of purchase access. Consumers tend to choose local products over imports. The main distribution channels preferred by consumers include supermarkets, online stores, and grocery stores. The product has great potential to compete in the market. Recommended marketing strategies include consumer education, brand image strengthening, and distribution expansion. The implications of the results of this study are the product of coconut aminos “Gulapa” has a fairly broad market opportunity, a clear marketing strategy direction, and the need for continuous market education. With the proper approachment, coconut aminos “Gulapa” could be the main choice as a substitute for traditional soy sauce in Indonesia.